Analysis of the key factors for successful public policy implementation: A qualitative study in Slovenia - Žiga Kotnik; Lan Umek; Polonca Kovač; Dalibor Stanimirović; Mirko Vintar (DANUBE: Law, Economics and Social Issues Review, 2020)
This paper analyses the role and significance of the selected factors for the successful design and implementation of public policies in Slovenia and more broadly. Based on structured interviews and content analysis of the responses, we investigated the impact of predefined factors (i.e. strategic, institutional, normative, economic/financial, methodological/procedural, organisational/human resources/ICT support factors). The aim of the article is to analyse the case of Slovenia, to identify which factors contribute most to the successful design and implementation of public policies, and to provide a basis for comparison with similar countries or systems. The research findings imply several conclusions, particularly strategic factors, which have been identified as the most essential. The other findings are related to the lack of evaluation practice, the discontinuity of and early changes in government, which affect all aspects of policy execution and lead to poor intersectoral collaboration as well as insufficient and ineffective public debate. Not surprisingly, all of the identified hindrances are featured in the pertinent theories as necessary democratic dimensions of contemporary public governance. Contrary to the national context, the EU influence seems to expedite policymaking processes and contribute to the consistency of policies.
Keywords: 330; Public Policy; Content Analysis; Good Governance; Evaluation; Strategic Factors